Statistical methods to apportion the sources of particles in the industrial region of Estarreja—Portugal - Borrego, C. (1991)
Factor analysis models are very attractive for source apportionment and have been widely applied. They do not require a priori knowledge of the number and composition of the sources, and they can actually uncover previously unsuspected sources and estimate the composition of the sources using only ambient monitoring data.